Las artes plásticas como medio en la construcción del aprendizaje significativo en los estudiantes del quinto grado de la escuela de educación general básica Manuel Salcedo de la parroquia Eloy Alfaro, ciudad de Latacunga - Tubón Saquinga, Ana Leticia (2016)
The present investigation was executed whit the children of 5th year of basic education of the School Manuel Salcedo, taking in consideration the possibilities that helped to create a process of teaching and learning collaborative where participate the director, the students and teachers of the institution with a investigation truthful for the development of the thesis while that the purpose of the quest has as proffer the desing and application of a workshop of motivating activities through the plastic arts and to develop the creative part of the right hemisphere, therefore favors to the brain development and integral of the brain providing to a significant learning of the own knowledge of the students, for it was necessary to analyze the problem of the Institution for your respective process….